Thermal and economic performance assessments of waste cooking oil /kerosene blend operated pressure cook-stove with porous radiant burner. (1st September 2020) - Kaushik, Lav Kumar; Muthukumar, P.
Abstract: Present energy and environmental scenario have been driving researchers to find alternative and renewable energy-based cooking sources. Inspection of Waste Cooking Oil (WCO) as alternative cooking fuel in a pressure cook-stove is the main focus of the present work. Comparative performance assessment of Conventional Kerosene Pressure Stove and Porous Radiant Burner (PRB) based Kerosene Pressure Stove fuelled with blends of WCO and kerosene are presented in this article. Three blend samples (volume % of kerosene and WCO) viz., BS1 (90/10), BS2 (75/25) and BS3 (50/50) have been used for investigation. Emissions (CO and NOx ) and efficiencies have been measured to learn about the burners thermal performance and to get additional insight, Control Cooking Test and Techno-economic Assessment have also been performed. Experimental results show that both the stoves are operational up to "BS3 " blend sample. In the operational input power range of 1.5–3 kW, with maximum WCO blending, thermal efficiency varied in the range of 45.3–37.8% and 36.2–28.6%, for PRB and conventional cook-stove, respectively. In the case of the stove with PRB, the maximum percentage reduction in CO and NOx emissions are 60% and 83%, respectively, which proves the burner ability to mitigate emissions. Saving in cooking time of 49 min and fuel consumption of 59% on daily basis by the use of PRB also shows its superiority. For a life span of 10 years, the economic assessment of the stove shows that annual savings, cumulative present worth of annual savings, Internal Rate of Return and payback period of the newly developed stoves are $29.93, $244.97, 268.5% and less than five months, respectively. The overall performance assessment shows improved results in all three fronts of energy, emissions, and economy, and suggests WCO can be a potential alternative cooking source when used in PRB. Highlights: Reported waste cooking oil combustion in novel Porous Radiant Burner. Up to 50% blending of Waste Cooking Oil with kerosene sustains stable combustion. Improvement in thermal efficiency of 9% with Porous Radiant Burner is achieved. Substantial reduction in CO and NOx emissions due to Porous Radiant Burner. Reduction in daily cooking time of 49 min and annual saving of $244.97 are achieved.